Analysis of Preference Level and Quality of Gembili Flour (Colocasia Esculenta L) as a Substitution for Wheat Flour in The Production of Crispy Brownies - Yulianto, Gunawan; Istiraharsi, Yedna (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
Brownies are one of the most popular bakery products, typically made from wheat flour, sugar, and fat, which often results in products high in calories and low in fibre. Along with the growing demand for healthy and functional foods, research on flour substitution in bakery products has expanded, including the use of local food sources. Dioscorea esculenta L. (gembili) is a local tuber rich in dietary fibre and inulin, with potential as an alternative flour to reduce dependence on imported wheat and support food diversification. This study aims to analyse consumer acceptance and sensory quality of crispy brownies formulated with gembili flour as a partial substitute for wheat flour. An experimental method was employed by producing crispy brownies in three stages of formulation: the first with gembili flour only, the second with added margarine, sugar, and baking powder, and the third with additional cocoa powder. Ten student panellists and three food experts evaluated the products through organoleptic and hedonic tests, focusing on attributes of aroma, taste, texture, and colour. The results show that the initial formulation produced a bitter taste and a less crispy texture. Improvements in the second and third formulations successfully enhanced crispiness, flavour balance, and colour intensity. Hedonic tests indicated that 80% of respondents “strongly liked” and 20% “liked” the crispy brownies with gembili flour, with no negative responses. These findings suggest that gembili flour can be used as a viable substitute for wheat flour in crispy brownies, maintaining sensory acceptance while providing additional nutritional value. This study highlights the scientific contribution of introducing gembili flour in modern bakery innovation and its practical potential to support local farmers, food diversification, and healthy eating trends.